Pagdaong revitalizing Los Baños downtown waterfront through an integrated ferry terminal and tourist center as a new gateway - Hamto, Norman R.; Santos, Frederick C. (Quezon City College of Architecture, University of the Philippines Diliman, 2020)
Los Baños is known for its unique harmony of science and nature except its downtown waterfront bordering Laguna de Bay, which faces an urban decline. Three factors were determined that contribute to its deterioration: rapid urbanization in the town, change in the uses of the waterfront areas resulting to inaccessibility, and the presence of tourists in destinations away from the downtown. The study aims to come up with an architectural solution that will catalyze the revitalization of the Los Baños población through transportation and tourism. This was answered by a proposed integrated ferry terminal and tourist center that will serve as a new gateway to the town. With the application of urban gateway concept and compact design, the project offers a facility that welcomes the tourists while also enhancing the accessibility of the waterfront. All of these are manifested through design strategies such as arrangement of spaces, establishing the facility’s unique character, and creation of lakeside public areas. Key features are provided in each of them that overall reflects the context of the site.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Ferry terminal -- Los Banos; Terminals (Transportation) -- Los Banos; Tourist center -- Los Banos; Waterfronts -- Los Banos